POLITICAL RHETORIC AND METAPHOR OF HISTORY: THE POETIC ENTELECHY OF HUGO VON HOFMANNSTHAL IN HIS TIME (Journal of Teleological Science, 2021)
The Austrian writer Hermann Broch dedicated one of his most famous literary essays, at the same time endowed with a profound philosophical reflection, to Hugo von Hofmannstahl, titling it Hugo von Hofmannstahl and his time. Starting from that Brokian goal that Hofmannstahl noted as being, in the sense of ansein, and the unfolding of a real interweaving of motions and passions, of fiery expressions and interiority that often remain unacknowledged, in the same way as can often happen in writing and in art in general, the aim here is to seek a unitary and substantial convergence between historical truth and literary testimony in order to arrive at an encounter of poetic thought and Hofmannstahl's final writing, characterizing it in his time, that Zwischenkriegszeit which he reached, in his clearest poetic and philosophical reflection, just when European destinies, from a political, cultural and civil point of view, found themselves being managed in the midst of disorder and chaotic totalitarian emphasis, which came to shape the bleakest European disintegration since the French Revolution and to characterize a collective tragedy.